(untitled) (Economics and region, 2020)
In the article the authors explore business processes in manufacturing enterprises. The main business processes of the production enterprise are defined and characterized. The main tasks that are key-note for business processes at the production level are formed. The authors establish the main functions of the administration process at the manufacturing enterprise. It is proposed to use the Business Process Modeling Notation (BPMN) standard, which will allow businesses to understand themselves and their business participants and allow organizations to quickly adapt to new internal and business situations of business. In conditions of competition, the requirements increase not only for staff but also for the management system, which is transformed into professional management (involving not only the implementation of tasks, but also the achievement of goals and the rational use of all resources). However, in recent years, increasing requirements for the quality of functional tasks and the need for their optimization in all departments, are structural units of the enterprise. Therefore, the administration of a manufacturing enterprise involves streamlining all material and information flows in the enterprise in order to make a profit and create the conditions for sustainable development. The business process management in the enterprise is an approach to management, which focuses on optimizing the implementation of business processes in organizations. Based on Business Process Modeling Notation, visual modeling of business processes is possible. The software toolkit for this international standard is IBM WebSphere Business Modeler, which contains a simulation mechanism and allows you to simulate the created business process models. For each task in the process, execution time, cost and other characteristics are assigned, which can be variables. The essence of simulation is that the input of the created business process model receives a given number of requests in a certain time interval. The number of requests corresponds to the number of times that the process must be completed. Accordingly, when processing the next request, statistics on the execution of various stages of the business process are accumulated. The collected statistics allow to analyze the compliance of satisfaction with the requirements. In IBM WebSphere Business Modeler, analysis can be performed for the entire process, resources, tasks, and queues before and after modeling. IBM WebSphere Business Modeler provides the ability to visualize, analyze, and document business processes. In order to continuously improve, you can model business processes, and then implement and monitor them, taking certain measures based on key performance indicators (Key Performance Indicators, KPI). Thus, business processes will be closely linked to strategic goals and will need to be adjusted as needed, which is very convenient in the face of rapid changes in the business environment. This will increase the efficiency of business processes of the manufacturing enterprise and facilitate the adaptation of the operating system to market requirements.